Combined fluorescent measurements, parallel factor analysis and GC-mass spectrometry in evaluating the photodegradation of PAHS in freshwater systems. (April 2021) - Seopela, Mathapelo Pearl; Powers, Leanne C.; Clark, Cheryl; Heyes, Andrew; Gonsior, Michael
Abstract: To better understand the transformation and photochemical fate of PAHs in aquatic environments, a custom-designed closed-circuit recirculation photodegradation system, combined with inline semi-continuous fluorescence and absorbance measurements, as well as modelling of excitation-emission (EEM) measurements with parallel factor analysis (PARAFAC), and GC-MS analysis, were combined to create a robust tool for holistically assessing the photodegradation of individual PAHs, their mixtures and photoproduct formation. Selected compounds included in the US EPA priority list, representing 2- to 6-ring compounds, were monitored individually and in mixtures, during 24 h photodegradation experiments. Experiments were conducted in solutions simulating ideal (ultrapure water) and environmentally relevant conditions (1.00 mg L −1 Suwannee River Natural Organic Matter (SRNOM)). The fluorescence, primary PARAFAC components and quantification data obtained by GC-MS, indicated that the decline in parent molecule concentration occurred rapidly within 200 min. The degradation rates of parent PAHs increased with aromaticity (6-ring ≫ 2-ring PAHs) and followed pseudo-first order degradation kinetics. The presence and transformation of degradation products, were captured by PARAFAC. NOM influenced the diversity of photoproducts. From the GC-MS results, photoproducts were only detected in Ant, BAnt and the PAH mixture solutions, but optical property analyses indicated that diverse changes occurred with all PAHs. Spectrometric and chromatographic data demonstrated that parent PAHs and photoproducts co-existed at various stages, which is significant for freshwater systems contaminated with these compounds if photoproducts have higher-toxic potential. These results may be used to model the hazard-potential associated with PAHs present in freshwater systems and understanding the mechanisms that govern their environmental fate. Graphical abstract: Image 1 Highlights: Combined FLD, PARAFAC and GC-MS analysis. Degradation increases with PAH aromaticity. Co-existence of parent compounds and photoproducts. NOM decelerates degradation and photoproduct identity.